2008
DOI: 10.1155/2008/846304
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Transition Metal Doping on the Photooxidation Process of Titania‐Clay Composites

Abstract: Montmorillonite- composites containing various transition metal ions (silver, copper, or nickel) were prepared, and their photocatalytic efficiencies were tested in the degradation of ethanol vapor at 70% relative humidity. Two light sources, UV-rich ( = 254 nm) and visible ( = 435 nm), were used. The kinetics of degradation was monitored by gas chromatography. It was established that, in the case of each catalyst, ethanol degradation was more efficient in UV-C ( = 254 nm) than in visible light, furthermore, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…1, the impurities such as illite, quartz and feldspar remained in the Ag-B, Cu-B and Fe-B samples. Menesi et al[47] also observed the similar changes after treatment of smectite with silver, copper and iron nitrate solutions.…”
mentioning
confidence: 58%
See 1 more Smart Citation
“…1, the impurities such as illite, quartz and feldspar remained in the Ag-B, Cu-B and Fe-B samples. Menesi et al[47] also observed the similar changes after treatment of smectite with silver, copper and iron nitrate solutions.…”
mentioning
confidence: 58%
“…This shows that copper ions can be incorporated between the silicate layers and produce well-oriented lamellar structure[47]. In addition, Ag-B, Cu-B and Fe-B samples showed a decrease in the intensities of the other reflections of montmorillonite (4.48 and 2.57 Å ), indicating the compositional change within the bentonite after the exchange of heavy metals and a loss of crystallinity of the smectite.…”
mentioning
confidence: 91%
“…Chemically, clays are hydrous aluminum silicates, ordinarily containing impurities, for example, potassium, sodium, calcium, magnesium, or iron in small amounts [33]. Every soldier should be well educated in terms and methods of hasty decontamination.…”
Section: Rapid Decontamination Of Personnel and Personal Gearmentioning
confidence: 99%
“…The Na-ions were exchanged with copper nitrate (1 mmol g -1 clay). The compositions of the catalysts prepared for thin film of ~1 µm thickness were the following: 20/80, 35/65, 50/50, 75/25 Cu-clay/TiO 2 ratio [26].…”
Section: Sample Preparationmentioning
confidence: 99%
“…700 ml) at 25 ± 0.1°C. The experimental setup and schematic drawing of the photoreactor are described in our previous papers [26,27]. The light sources of the reactor were two types of 15 W low pressure mercury lamp (LightTech, Hungary), at λ max = 254 nm and λ max = 435 nm wavelength.…”
Section: Sample Characterisationmentioning
confidence: 99%